Results obtained with the jejunal diverticular loop of Praderi in biliary digestive anastomosis - Estefan, Alberto; Cardozo, Tabaré; Baldizán, Jorge; Olmedo, Mario; Di Donna, Bruno; Acosta, Fernando (Cirugía del Uruguay, 1986)
Analysis ol results obtained with the use of Praderi's diverticular ansa in biliary-digestive anastomosis. For that purpose, a retrospective study was carried out of 183 cases of biliary-jejunal anastomosis in which Praderi's ansa was used. In no case morbi-mortality could be ascribed to the use of said jejunal ansa. The autor concludes that in most cases this is the choice for a jejunal ansa when biliary-jejunal anastomosis must be performed.